2022
DOI: 10.1002/1878-0261.13306
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest‐specific protein 2 (GAS2) interacts with CXCR4 to promote T‐cell leukemogenesis partially via c‐MYC

Abstract: Although growth arrest‐specific protein 2 (GAS2) promotes the growth of T‐cell acute lymphoblastic leukemia (T‐ALL) cells in culture, the effect of GAS2 on T‐cell leukemogenesis has not been studied, and the mechanism remains unclear. In the present study, xenograft studies showed that GAS2 silencing impaired T‐cell leukemogenesis and decreased leukemic cell infiltration. Mechanistically, GAS2 regulated the protein expression of C‐X‐C chemokine receptor type 4 (CXCR4) rather than its transcript expression. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Metabolic changes similar to the Warburg effect occur in the context of in ammation induction. Recent studies on c-MYC have identi ed it as a key factor in tumor metabolism immunity and a major regulator of metabolic reprogramming, stimulating glycolysis, nucleotide metabolism, and glutamine metabolism [37,52].Although some studies have indicated that silencing CXCR4 in T-cell acute lymphoblastic leukemia can inhibit the expression of myc [53]. However, we rst demonstrated the transcriptional regulation of Pfkfb3 by MYC in macrophages.…”
Section: Discussionmentioning
confidence: 78%
“…Metabolic changes similar to the Warburg effect occur in the context of in ammation induction. Recent studies on c-MYC have identi ed it as a key factor in tumor metabolism immunity and a major regulator of metabolic reprogramming, stimulating glycolysis, nucleotide metabolism, and glutamine metabolism [37,52].Although some studies have indicated that silencing CXCR4 in T-cell acute lymphoblastic leukemia can inhibit the expression of myc [53]. However, we rst demonstrated the transcriptional regulation of Pfkfb3 by MYC in macrophages.…”
Section: Discussionmentioning
confidence: 78%